'Forget everything you have ever learned about art, and start from the beginning': Charismatic leadership and art school teaching. Issue 2 (1st December 2014) - Owen, Chris
This article explores the nature of the art and design lecturer's role in relation to Weber's definition of charismatic leadership, and to more recent theories of transformational leadership. By reference to historical examples, the author analyses the process by which the charismatic art and design lecturer can influence students, and when necessary overcome their resistance to change. Using French and Raven's model of social power, the author goes on to investigate the contribution made by charisma to the lecturer's power to persuade, even when the lecturer may be committed to using a constructive model of the educational process. Finally, the article explores the potential of 'frame alignment' as a strategy by which charismatic lecturers can overcome the reluctance of some students to open themselves to new ways of thinking and working.